2018
DOI: 10.1016/j.gde.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

circRNAs in Cancer

Abstract: Exonic circular RNAs (circRNAs) are mostly generated from exons of protein-coding genes and, in many cases, are more abundant that the linear product from their hosting gene. Certain circRNAs are very abundant in the brain and in non-dividing cells; and many also show physiological-specific and tissue-specific expression. Moreover, recent work has demonstrated that some circRNAs are functional. Lately an important number of research articles have pointed a relation between cancer and certain circRNAs. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
337
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(340 citation statements)
references
References 50 publications
3
337
0
Order By: Relevance
“…Numerous studies have demonstrated that circRNAs can play a regulatory part in the translation and binding of miRNAs and so forth (Beermann, Piccoli, Viereck, & Thum, 2016). On the other side, increasing evidence have proved circRNAs are involved in a variety of carcinoma activities, like viability, apoptosis, and so on (Patop & Kadener, 2018). circFNDC3B is a circRNA shears from FNDC3B, which has been presented to play a promoting or restraining efficacy in carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that circRNAs can play a regulatory part in the translation and binding of miRNAs and so forth (Beermann, Piccoli, Viereck, & Thum, 2016). On the other side, increasing evidence have proved circRNAs are involved in a variety of carcinoma activities, like viability, apoptosis, and so on (Patop & Kadener, 2018). circFNDC3B is a circRNA shears from FNDC3B, which has been presented to play a promoting or restraining efficacy in carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A subset of circRNA produces proteins in the fly brain and in murine and human cells Pamudurti et al, 2017;Yang et al, 2017), and others seem to be related to the immune response (Li et al, 2017a;Liu et al, 2019). In addition, a number of studies suggest an association between circRNAs and cancer (reviewed in Kristensen et al, 2018;Patop & Kadener, 2018). In addition, a number of studies suggest an association between circRNAs and cancer (reviewed in Kristensen et al, 2018;Patop & Kadener, 2018).…”
mentioning
confidence: 99%
“…Several reports demonstrated in vivo functions for circRNAs in the mouse and fly brains, as well as in bone marrow (Piwecka et al, 2017;Kleaveland et al, 2018;Xia et al, 2018;Data ref: Pamudurti et al, 2018). In addition, a number of studies suggest an association between circRNAs and cancer (reviewed in Kristensen et al, 2018;Patop & Kadener, 2018). These developments show a clear change of view in the scientific community toward circRNAs, representing a turning point in this exciting and rapidly developing field.…”
mentioning
confidence: 99%
“…It is clear that circRNAs have an important function in progression and development of cancer and influence cancer markers . But, the roles of circRNAs in NSCLC are largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that circRNAs have an important function in progression and development of cancer and influence cancer markers. [25][26][27][28] But, the roles of circRNAs in NSCLC are largely unclear. In the current investigation, we confirmed that circPIP5K1A was upregulated in NSCLC.…”
Section: Discussionmentioning
confidence: 99%